Non-psychotropic phytocannabinoid interactions with voltage-gated sodium channels: An update on cannabidiol and cannabigerol - Ghovanloo, Mohammad-Reza; Dib-Hajj, Sulayman D.; Goodchild, Samuel J.; Ruben, Peter C.; Waxman, Stephen G. (Frontiers in Physiology, 2022)
Phytocannabinoids, found in the plant, Cannabis sativa, are an important class of natural compounds with physiological effects. These compounds can be generally divided into two classes: psychoactive and non-psychoactive. Those which do not impart psychoactivity are assumed to predominantly function via endocannabinoid receptor (CB) -independent pathways and molecular targets, including other receptors and ion channels. Among these targets, the voltage-gated sodium (Nav) channels are particularly interesting due to their well-established role in electrical signalling in the nervous system. The interactions between the main non-psychoactive phytocannabinoid, cannabidiol (CBD), and Nav channels were studied in detail. In addition to CBD, cannabigerol (CBG), is another non-psychoactive molecule implicated as a potential therapeutic for several conditions, including pain via interactions with Nav channels. In this mini review, we provide an update on the interactions of Nav channels with CBD and CBG.